CROSS-BORDER CO-OPERATION EUROREGIONS IN THE ROMANIAN DANUBE BORDER-ZONE - RADU SĂGEATĂ; MIHAELA PERSU (Revue Roumaine de Géographie)
Since several transversal issues have been cropping up, the need was felt for a unitary system to tackle them. So, the building of some cross-border co-operation structures both at local level (cross-border zones) and at regional level (cross-border Euroregions) appeared as highly necessary and desirable. Their typology depends on the intensity and character of cross-border fluxes, the existence of local convergence cores, and of elements of complementariness and homogeneity between the frontier spaces. The Danube-lined Romanian frontier represents an axis of discontinuity between natural regions, each with its own distinct traits. As a result, the limitrophe border zone shows particular social and economic characteristics. Although the Danube River has favoured the emergence of an urban area, yet the respective towns do not form a coherent system, the zone itself being extremely rural as a whole. The Romanian cross-border zone in the Danube sector features by a sudden variation in transversal fluxes, concentrating on certain directions imposed by the pattern of communication routes and the layout of doublet towns.